2014
DOI: 10.1103/physrevb.89.075425
|View full text |Cite
|
Sign up to set email alerts
|

Connecting electron and phonon spectroscopy data to consistently determine quasiparticle-phonon coupling on the surface of topological insulators

Abstract: Photoemission and phonon spectroscopies have yielded widely varying estimates of the electronphonon coupling constant λ on the surfaces of topological insulators, even for a particular material and technique. We connect the results of these experiments by determining the Dirac fermion quasiparticle spectral function using information from measured spectra of a strongly-interacting, low-lying optical surface phonon band. The manifest spectral features resulting from the coupling are found to vary on energy scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…144,160,161 Whether Kohn anomalies at a phonon momentum that connects opposite sides of a topological Dirac cone are possible, is still an open question as it would require a phonon-induced transition involving a spinflip. 144,160,162,163 The latter may become possible by creating or annihilating a phonon which carries an angular momentum of 1 quantum number. While Kohn anomalies have been reported in the lower part of the phonon spectrum of TIs, 155,160,162 recent studies have shown that the major contribution to e-ph coupling in these materials comes from polar optical modes.…”
Section: Specific Science Cases For Combined Has/hese Investigationsmentioning
confidence: 99%
“…144,160,161 Whether Kohn anomalies at a phonon momentum that connects opposite sides of a topological Dirac cone are possible, is still an open question as it would require a phonon-induced transition involving a spinflip. 144,160,162,163 The latter may become possible by creating or annihilating a phonon which carries an angular momentum of 1 quantum number. While Kohn anomalies have been reported in the lower part of the phonon spectrum of TIs, 155,160,162 recent studies have shown that the major contribution to e-ph coupling in these materials comes from polar optical modes.…”
Section: Specific Science Cases For Combined Has/hese Investigationsmentioning
confidence: 99%
“…As electron-phonon interactions are ubiquitous in real materials and can affect properties such as transport of surface states, we now consider the impact of such interactions on the Chern insulator [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In particular, we consider the deformation potential coupling between an acoustic phonon mode and spinless fermions of the form [57]…”
Section: Chern Insulator With Electron-phonon Interactionmentioning
confidence: 99%
“…Furthermore, we apply the emergent theory to the specific EPI with the 7meV optical phonon mode [21,22]. Our work therefore builts a theoretical bridge between the electron-optical phonon coupling experiments in Ref's [21,22] and the in-plane spin anomaly experiments in Ref. [34].…”
Section: Introductionmentioning
confidence: 97%
“…The electron-disorder interaction remains the dominant mechanism affecting the low energies and low temperatures where the e-ph interaction is suppressed. The coherent helium-atom-scattering experiments [21][22][23]28] in a wide range of temperatures (100 < T (K) < 300) indicated the presence of the optical EPI pointing at a strong softening of the 7meV phonon mode. The position of the softening at the phonon momentum near 2k F points at a Kohn anomaly and thus a strong coupling of the optical branch to the electronic states [28] with a less significant role played by the acoustic phonons [12,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation